The Lord Is My Shepherd: Psalms to Accompany Us on Our Journey through Aging - Baumstein, Paschal (Cistercian studies quarterly, 2005)
Reviews the book "The Lord Is My Shepherd: Psalms to Accompany Us on Our Journey Through Aging," by Albert Michah Lewis.